ANALISIS MAKNA SIMBOLIK DALAM TUTURAN RITUAL KEMATIAN JINGITIU DI SABU RAIJUA - Sarlin Sarlota Lelo Djeru; Labu Djuli; Margareta P. E. Djokaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the symbolic meanings in the Jingitiu death ritual discourses among the Sabu Raijua community. The study was motivated by the continued preservation of the Jingitiu death ritual, which incorporates traditional discourses with cultural symbols that reflect the belief system and values of the Sabu community. The study employs a qualitative descriptive method using Charles Sanders Peirce’s semiotic approach. Data in the form of ritual discourses were collected through observation, interviews with traditional leaders and community members, and documentation in Raedewa Village, West Sabu Subdistrict, Sabu Raijua Regency. Data analysis was conducted through identification, classification, and interpretation based on the categories of icon, index, and symbol, followed by the drawing of conclusions. The research findings indicate that the symbolic meaning in the Jingitiu death ritual discourse is manifested through three categories of signs. Icons include the water of life, adju herai (a wooden support), and provisions for the spirit. Indices are evident in the purification of the corpse, the binding of sins, the digging of the grave, and the liberation of the spirit. Symbols represent the spirit’s journey, purity, self-purification, and family reverence. In conclusion, the Jingitiu death ritual discourse serves not only as a means of traditional communication but also as a medium for transmitting religious values, honoring ancestors, and preserving the cultural identity of the Sabu Raijua community.